Web GIS : principles and applications - Fu, Pinde, 1968-; Sun, Jiulin (Redlands, Calif. : ESRI Press, 2011)
This book offers a balance of principles, concepts, and techniques to guide readers toward an understanding of how the World Wide Web can expand and modernize the way you use GIS technology.--[book cover]
Includes bibliographical references ( p. 278-280) and index.
Keywords: Geographic information systems; Geography -- Computer network resources; World Wide Web